Hydrotropic Solubilization: An Emerging Approach - Kuchekar, Ashwin Bhanudas; Gawade, Ashwini; Boldhane, Sanjay (Journal of Drug Delivery and Therapeutics, 2021)
Drug development plays an important role in patient safety and effectiveness. The therapeutic suitability of a new drug depends on the solubility. The solubility of the sparingly soluble drug remains a problem in identifying new active compounds. Solubility plays an important role in achieving optimal drug concentration. Low solubility is not only a concern for the production of formulations, but also an obstacle from the outset when identifying active chemicals for therapeutic purposes. Due to its simplicity in terms of ease of administration and economy, the oral route is the preferred route of drug administration over other routes. Effective aqueous solubility is the first prerequisite for oral medication, since low solubility has poor absorption and bioavailability and unpredictable toxicity of the gastrointestinal mucosa. To avoid these crises, different methodologies are used to improve the solubility and bioavailability of poorly soluble drugs, and hydrotropic solubilization is one of them. Hydrotropic agents have the potential to improve the solubility of water-insoluble drugs. In this review, we try to address hydrotropic solubilization methodologies.Keywords: Hydrotropy, Micelles, Solubility, Formulation.